Impact of reimbursement systems on patient care – a systematic review of systematic reviews - Wagenschieber, Eva; Blunck, Dominik (Health Economics Review, 2024)
Background: There is not yet sufficient scientific evidence to answer the question of the extent to which different reimbursement systems influence patient care and treatment quality. Due to the asymmetry of information between physicians, health insurers and patients, market-based mechanisms are necessary to ensure the best possible patient care. The aim of this study is to investigate how reimbursement systems influence multiple areas of patient care in form of structure, process and outcome indicators. Methods: For this purpose, a systematic literature review of systematic reviews is conducted in the databases PubMed, Web of Science and the Cochrane Library. The reimbursement systems of salary, bundled payment, fee-for-service and value-based reimbursement are examined. Patient care is divided according to the three dimensions of structure, process, and outcome and evaluated in eight subcategories. Results: A total of 34 reviews of 971 underlying primary studies are included in this article. International studies identified the greatest effects in categories resource utilization and quality/health outcomes. Pay-for-performance and bundled payments were the most commonly studied models. Among the systems examined, fee-for-service and value-based reimbursement systems have the most positive impact on patient care. Conclusion: Patient care can be influenced by the choice of reimbursement system. The factors for successful implementation need to be further explored in future research.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Bundled payment; Fee-for-service; Outcome; Patient treatment; Pay-for-performance; Process; Reimbursement; Structure; Systematic review